Google Docs to Manage an EFL Writing Class: How It Helps and What to Prepare - Kurniawati, Atin (Journal of English and Education (JEE), 2022)
Google Docs has been reported by many researchers as a tool that facilitates EFL students’ performance enhancement in writing class, but the facts in using this tool from teachers’ point of view in managing a writing class still lack attention. This article aims to describe how Google Docs can assist EFL teachers in managing writing classes as well as the strategies that can be carried out to optimize the use of this tool. Using narrative inquiry, this study employed a teacher’s narratives and documentation of activities on Google Docs. Thematic coding was done to highlight meaningful experiences. It revealed that Google Docs assisted both students and teachers in terms of proofreading, giving feedback, and recording students’ activities. However, during the use of this tool, sort of challenges might hinder students’ progress, such as students’ ignorance of the helpful features and failure in complying with the instructions. Therefore, English teachers can prepare some strategies i.e. giving clear rules and instructions, having conferences and synchronous interaction more often on Google Docs, and building up students’ responsibility for the learning progress. It implies that technology itself doesn’t guarantee students’ improvement in writing, but teachers’ and students’ ability and responsibility in using the technology contribute more to the progress.